2014
DOI: 10.1091/mbc.e14-05-0971
|View full text |Cite
|
Sign up to set email alerts
|

TheCaenorhabditis elegansSUN protein UNC-84 interacts with lamin to transfer forces from the cytoplasm to the nucleoskeleton during nuclear migration

Abstract: The nucleoplasmic domain of the Caenorhabditis elegans SUN protein UNC-84 interacts with lamin. If this interaction is disrupted, a partial failure in nuclear migration occurs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 70 publications
1
61
0
Order By: Relevance
“…Mutations that affect the nucleoplasmic part of UNC-84 cause milder hypodermal nuclear migration defects than complete null alleles (Malone et al 1999;Bone et al 2014). Nevertheless, a single amino acid substitution in UNC-84 (P91S; e1411), which reduces its interaction with LMN-1 in the yeast two-hybrid assay, or depletion of LMN-1 by RNAi, induces a significant migration defect, highlighting the relevance of the nuclear lamina in LINC activity (Bone et al 2014).…”
Section: Mechanotransductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations that affect the nucleoplasmic part of UNC-84 cause milder hypodermal nuclear migration defects than complete null alleles (Malone et al 1999;Bone et al 2014). Nevertheless, a single amino acid substitution in UNC-84 (P91S; e1411), which reduces its interaction with LMN-1 in the yeast two-hybrid assay, or depletion of LMN-1 by RNAi, induces a significant migration defect, highlighting the relevance of the nuclear lamina in LINC activity (Bone et al 2014).…”
Section: Mechanotransductionmentioning
confidence: 99%
“…Nevertheless, a single amino acid substitution in UNC-84 (P91S; e1411), which reduces its interaction with LMN-1 in the yeast two-hybrid assay, or depletion of LMN-1 by RNAi, induces a significant migration defect, highlighting the relevance of the nuclear lamina in LINC activity (Bone et al 2014). In parallel to LMN-1, the conserved transmembrane NE protein SAMP-1 also contributes to nuclear migration, but by unknown mechanisms (Bone et al 2014). Interestingly, a recent study measured mechanical responses to external physical tension and found a significant increase in hypodermal nuclear stiffness in animals depleted for UNC-84 (Zuela et al 2016).…”
Section: Mechanotransductionmentioning
confidence: 99%
“…SUN and KASH proteins interact via conserved domains at their C-termini in the PNS. 5 SUN proteins interact with lamins in the nucleoplasm 6,7 and KASH proteins recruit cytoskeletal components to the ONM. 8 In this way, LINC complexes stabilize the nuclear envelope against cytoplasmic forces and facilitate nuclear positioning in a variety of cellular processes, including cell division, establishment of cellular polarity, fertilization, cellular migration, and differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, kinesin-1 provides the major force to drag the nucleus towards the plus-end of MTs, whereas dynein fine-tunes the process by imposing smaller amplitude movements in the opposite direction . The mechanical forces exerted by the cytoskeleton are probably transmitted to the nucleoskeleton through a specific interaction between the SUN protein UNC-84 and the nuclear lamin, (Bone et al, 2014;Cain and Starr, 2015). Importantly, the molecular mechanism controlling nuclear positioning are evolutionary conserved, since the human LINC complex can partially rescue the hyp7 defective nuclear migration of double unc-83; unc-84 mutants (Cain et al, 2014).…”
Section: Mt-associated Proteinsmentioning
confidence: 99%